Hubungan Motivasi dengan Kepuasan Kerja Petugas Rekam Medis di Rumah Sakit Yadika Pondok Bambu Tahun 2015 - Tri Wulandari; Diana Barsasella (Jurnal Persada Husada Indonesia, 2016)
According to Stoner (1996) motivation is the cause and support the person's behavior. Robin (1989), stated motivation is the ability to struggle or strive to a higher level, provided they are not ignoring its ability to obtain satisfaction in the form of personal fulfillment. Job satisfaction is an assessment of how far the workers that the overall job or satisfy their needs and generally can be defined as a person's feelings towards their job. Job satisfaction is closely linked to the attitude of employees towards their own work, the work situation, cooperation between the leadership and with fellow employees. (As, ad, 2000). This study design is a research plan drafted in such a way, so that the study can obtain answers to questions (Setiadi, 2007). This research is quantitative. This research uses analytic survey research methods. Characteristics of respondents who most nation points in this study is the beginning of adult respondents age group (20-30 years) 11 (61.1%). Based on the gender of the most respondents were male as many as 13 (72.2%). The education level of most of the largest higher education as many as 11 (61.1%). Based on the educational background of the respondents it was found that non medical record as many as 17 (94.4%). Based on the long work of the most respondents was the same between the new work with old works as many as nine (50%). Based on the intrinsic motivation that most respondents was that as many as 10 (55.6%). Based on extrinsic motivation is a good majority of respondents ie 13 (72.2%). Based on job satisfaction of the most respondents are satisfied with 11 (61.1%). From the results of statistical test by using t-test is a statistical test two samples are independent (independent sample t-test) there is no difference between each variable.